2005
DOI: 10.1002/gps.1288
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of depression in late life: a population based study from a rural Greek town

Abstract: In a rural Greek area, the prevalence of depression in late life is high. Depression was more common among unmarried individuals, those with significant cognitive impairment, and in association with specific medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
3
15

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 65 publications
10
64
3
15
Order By: Relevance
“…Many studies have reported that medical co-morbidity affects the feeling of well-being in late life and that chronic medical conditions increase the risk of depression (Cole and Dendukuri 2003;Djernes 2006;Bruce et al 2002). A study of older people in Greece also concurred with our finding (Papadopoulos et al 2005). Our multivariate analysis suggested there is no differences in vulnerability to this risk factor for depressive symptoms between men and women.…”
Section: Health Statussupporting
confidence: 88%
“…Many studies have reported that medical co-morbidity affects the feeling of well-being in late life and that chronic medical conditions increase the risk of depression (Cole and Dendukuri 2003;Djernes 2006;Bruce et al 2002). A study of older people in Greece also concurred with our finding (Papadopoulos et al 2005). Our multivariate analysis suggested there is no differences in vulnerability to this risk factor for depressive symptoms between men and women.…”
Section: Health Statussupporting
confidence: 88%
“…Furthermore, our data is not in agreement with the studies which argue that the elderly who do not have someone to confide in, or an intimate relationship, present a higher susceptibility for depressive symptoms (e.g. Chou & Chi, 2005, Papadopoulos et al, 2005, Silva & Sequeira, 2002Stek et al, 2006). This result may be related to the fact that the intimate and marital relationships, in the context of institutionalization, often assume specificities and limitations related to the way these nursing homes work.…”
Section: Discussioncontrasting
confidence: 99%
“…This result corroborates those of other studies (e.g. Gazalle et al 2004;Oliveira, 2005, Papadopoulos et al, 2005, in which age is considered a risk factor for the onset of depressive symptoms. These results may be related to the fact that, with advancing age, the elderly, particularly those in institutions, have less autonomy, less pleasant life experiences and more physical and sensory handicaps.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations